The answer to your questions is B. {(4, 2), (4, –2), (9, 3), (9, –3)} because you don't have a repeat of a number the X side which is your output. I hope that this is the answer that you were looking for and it has helped you.
15 I may be wrong but If I am please provide more information.
Answer:
y = (-1)x
Step-by-step explanation:
What you are to do here is to "rewrite -y - x = 0 in the slope-intercept form y = mx + b."
Start by solving -y - x = 0 for y: -y = x or y = -x.
Rewrite this by inserting the coefficient 1 and representing b by 0:
y = (-1)x + 0
which is equivalent to y = (-1)x
Asteroids, planets, moons, and astronomy.